Penanggulangan Gelandangan dan Pengemis - Napitupulu, Hasan Sah Putra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study discusses the implementation of Government Regulation No. 31 of 1980 article 2 regarding the prevention of homeless people and beggars in Padangsidimpuan City. This research is motivated by the existence of vagrants and beggars who are increasingly widespread whose existence reaches the residential community in Padangsidimpuan City, causing security, order and beauty problems in Padangsidimpuan City. This research is a field research using qualitative descriptive analysis method. The method of collecting data in this research is by means of interviews and documentation in accordance with the provisions contained in Government Regulation No. 31 of 1980 article 2 concerning the prevention of homeless people and beggars.The party being researched is the Padangsidimpuan City Social Service as the government in the Padangsidimpuan City environment. The results of the research by researchers that the implementation of Government Regulation No. 31 of 1980 Article 2 concerning the Prevention of Homeless and Beggars in Padangsidimpuan City has been carried out, this can be seen from the data on the existence of homeless and beggars, the Social Service of Padangsidimpaun City in the last three years experiencing a decline. And when viewed from the fiqh siyasah the government in overcoming homeless and beggars in Padangsidimpuan is still not optimal because there are no derivative rules from government regulation No. 31 of 1980 concerning the prevention of homeless and beggars in Padangsidimpuan City.